Pengaruh Promo di Aplikasi E-commerce Shopee terhadap Minat Beli Konsumen - winda octavia ramadhina; nadia rachmawati; Muhammad Alkirom Wildan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technology brings big changes for its users. Purchases can now be made online through e-commerce platforms. One of the popular platforms in Indonesia is Shopee, an online shopping application that is widely used by Indonesians. The purpose of this study was to find out about promos, the types of promos that are applied, shopee marketing strategies, factors supporting the effectiveness of promos, and challenges or risks of promo strategies at shopee. The results of this study consumers depend on promotions, which causes dependence on discounts before making purchases, resulting in reduced brand loyalty and purchases in the absence of promotions. About strategic promotion in e-commerce cannot be underestimated, because the role of promotion is very important in encouraging customer interest.